Evolution of magnesium during reactive milling under hydrogen atmosphere with crystallitic carbon as milling aid - Zhou, Shixue; Zhang, Qianqian; Ran, Weixian; Han, Zongying; Niu, Haili; Han, Shuna; Cui, Liqiang; Zhang, Tonghuan; Chen, Haipeng; Liu, Di (Journal of alloys and compounds, 2013)
•Shape of β-MgH2 nanoparticles from milling of Mg with H2 is oblique hexagonal prism.•Size increase of Mg particles from MgH2 dehydriding can be restrained by carbon.•Endothermic peak of γ-MgH2 is 53°C lower than that of β-MgH2 from 10 to 20h milling.•Heat absorption of γ-MgH2 dehydriding is 18kJ/mol H2 lower than that of β-MgH2. This paper is concerned with the changes of morphology, crystal structure and hydrogen storage properties of magnesium during reactive milling under hydrogen atmosphere with crystallitic carbon, which is prepared from anthracite coal by demineralization and carbonization, as milling aid. Experiments show that β-MgH2 of tetrahedral crystal structure with particle size of 20–60nm and geometric shape of oblique hexagonal prism predominates in the material from 3h of milling under 1MPa H2. Besides, there is γ-MgH2 of orthorhombic crystal structure in the materials from milling. The Mg particles from MgH2 dehydriding take the shape of right hexagonal prism. The carbon can prevent Mg particles from coalescing into big bulk during heating for hydrogen releasing. The endothermic peak of γ-MgH2 is 53°C lower than that of β-MgH2 in the materials from 10 to 20h of milling, and its heat absorption for dehydriding is 18kJ/mol H2 lower than that of β-MgH2.